Chick-fil-A : a corporate position on same-sex marriage - Prouty, Kasia; Spencer, Dana; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
In the summer of 2012, Chick-fil-A President and COO Dan Cathy sparked controversy by sharing his biblical views on family and marriage with the Ken Coleman radio show and the Baptist Press. At one point, he asked for God's mercy on a generation that holds "such a prideful, arrogant attitude" with "the audacity to define what marriage is all about" Advocates of same-sex marriage responded with a boycott, which then drew reactions from supporters of Cathy and traditional marriage. This case study explores the fallout after a corporate leader publicly speaks his mind on a contentious social issue.
Originally published in Prouty, K., Spencer, D., & ORourke, J. S. (2012). Chick-fil-A: A corporate position on same-sex marriage. 12-11. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Chick-Fil-A Corporation; Fast food restaurants -- Public relations -- Case studies; Corporate image -- Case studies